New perineal injection technique for pudendal nerve infiltration in diagnostic and therapeutic procedures - Weinschenk, Stefan; Hollmann, Markus W.; Strowitzki, Thomas (Archives of gynecology and obstetrics, 2016)
Purpose: Pudendal nerve injection is used as a diagnostic procedure in the vulvar region and for therapeutic purposes, such as in vulvodynia. Here, we provide a new, easy-to-perform perineal injection technique. Patients and methods: We analyzed 105 perineal injections into the pudendal nerve with a local anesthetic (LA), procaine in 20 patients. A 0.4 × 40 mm needle was handled using a stop-and-go technique while monitoring the patient’s discomfort. The needle was placed 1–2 cm laterally to the dorsal introitus. After aspiration, a small amount of LA was applied. After subcutaneous anesthesia, the needle was further advanced step-by-step. Thus, 5 ml could be applied with little discomfort to the patient. Anesthesia in the pudendal target region was the primary endpoint of our analysis. Results: In 93 of 105 injections (88.6 %), complete perineal anesthesia was achieved with a single injection. 12 injections were repeated. These injections were excluded from the analysis. Severity of injection pain, on visual analog scale (VAS) from 0 to 100, was 26.8 (95 % CI 7.2–46.4). Age (β = 0.33, p < 0.01) and the number of previous injections (β = 0.35, p < 0.01) inversely correlated with injection pain. Injection pain and anesthesia were not affected by BMI, the number and the side of previous injections, or order of injection. A reversible vasovagal reaction was common, but no serious adverse effects occurred. Conclusion: Perineal pudendal injection is an effective and safe technique for anesthesia in diagnostic (vulva biopsy) and therapeutic indications (pudendal neuralgia), and regional anesthesia in perinatal settings.
Published online: 15 September 2015
Gesehen am 09.06.2020